THE ROLE OF THE ECONOMIC AND INSTITUTIONAL FRAMEWORK IN ENSURING FINANCIAL STABILITY IN ROMANIA, DURING 2012-2014 - Cristian, IONESCU (Strategii Manageriale)
The aim of this paper is to empirically study the concept of financial stability in Romania, from both an economic and institutional perspective. In this paper, I analyze three main aspects: the macroeconomic performance of Romania, the developments of the structural reform and the policy instruments, related to two main domains: the monetary and exchange rate policies; and the priorities of the financial sector (the strengthening of the banks' balance sheets and supporting the Romanian economy). Therefore, this paper debates the policy instruments of Romania's institutions and authorities that aim to promote financial stability.